MEDIA SEBAGAI LOCUS THEOLOGICUS: REKONSTRUKSI MISSIO DEI DALAM PERSPEKTIF TEOLOGI DIGITAL - Enos Rembang; Jeinstira; Feronika; Esterlina Dodo; Fernando Randa Ma'dika (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
The development of digital media has brought significant changes in how the church understands, experiences, and implements God's mission (Missio Dei). This article aims to analyze the role of digital media as a locus theologicus and its implications for the reconstruction of Missio Dei from a digital theological perspective. The research method used is descriptive qualitative with a literature study approach, which includes analysis of books, journals, articles, and relevant church digital content. The results show that digital media is not just a communication tool, but a space for theological reflection where the proclamation of the Gospel, faith formation, and community interaction take place authentically and participatory. Digital media expands the reach of the mission, enabling inclusive congregational participation, while simultaneously demanding creative, innovative, and ethical communication strategies. On the other hand, emerging challenges include the risk of shallow messages, algorithmic dominance, and information distortion that can affect the quality of proclamation. These findings confirm that the integration of digital media in the practice of church mission has important theological and strategic implications for the contemporary church, so that the proclamation of the Gospel remains relevant, authentic, and contextual in the digital era